Assessing object-oriented programming skills in the core education of computer science and information technology: Introducing new possible approach - Khamis, N.; Idris, S.; Ahmad, R.; Idris, N. (2008)
Deciding on how to evaluate each students programming skills is one of the largest challenges facing educators who teach object-oriented courses. Traditional assessment of programming education is with Grade. Quite often students get good grades in programming but still facing great challenges or have difficulties to take on real programming jobs. This research focus on how we addressed this challenge in object oriented programming course by proposing a new assessment method to assess students' object-oriented programming skills. The process begins by identifying generic object-oriented skills that students should acquired. In this paper we discuss the issues on object-oriented programming assessment and our proposed solution for a new assessment model. This followed by an approach taken in the process of identifying the object-oriented skills using Delphi technique. Delphi technique is a structured multi-step process that uses a group of experts to achieve a consensus opinion. We present the methodology of three Delphi processes to identify object-oriented programming skills. The identified skills will be used to guide both the coverage of student learning assessments and can be used by instructors to identify what topics merit emphasis.